2014
DOI: 10.1111/1758-2229.12202
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial role in pine wilt disease development – review and future perspectives

Abstract: Mutualistic and beneficial relationships between nematodes and bacteria are highly present in nature, mostly occurring because of nutritional dependence and pathogen protection, and intrinsically related with the environment, the ecological conditions and the nematode life stages. Thirty-four years have passed since the first hypothesis suggesting a bacterial role in pine wilt disease (PWD), associated with the pinewood nematode (PWN), Bursaphelenchus xylophilus. In 1980, researchers reported that bacteria ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 73 publications
1
52
0
Order By: Relevance
“…The disinfected PWN multiplied slowly (1.7‐fold increase in population) when compared to the non‐disinfected PWN (4.6‐fold increase in population), 10 days after inoculation. These results show that the disinfection procedure greatly influences PWN viability as previously suggested (Nascimento et al ., ). H 2 O 2 used in the disinfection procedure is a reactive oxygen species (ROS), which may induce an exaggerated oxidative stress damage to the PWN, thus, limiting its reproduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disinfected PWN multiplied slowly (1.7‐fold increase in population) when compared to the non‐disinfected PWN (4.6‐fold increase in population), 10 days after inoculation. These results show that the disinfection procedure greatly influences PWN viability as previously suggested (Nascimento et al ., ). H 2 O 2 used in the disinfection procedure is a reactive oxygen species (ROS), which may induce an exaggerated oxidative stress damage to the PWN, thus, limiting its reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Oku et al (1980) proposed that bacteria carried by the PWN could contribute to PWD development through toxin production. Since then, many studies were conducted in order to understand the possible contribution of bacteria in PWD, and bacterial communities associated to the PWN isolated in different countries and from different pine trees were also described (reviewed in Nascimento et al, 2015). Several reports have shown that some PWN-associated bacteria were able to increase nematode reproduction, pathogenicity and also its resistance to xenobiotics, therefore, suggesting a symbiotic relationship between the PWN and its associated bacteria (Kawazu et al, 1996a;Zhao et al, 2003;Zhao and Lin, 2005;Cheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing debate on the role of bacterial communities associated to the PWN on PWD. Population variations of bacterial communities generally follow those of PWN progression (Xie and Zhao 2008;Roriz et al 2011;Nascimento et al 2014) and evidence as pointed towards being potential triggers for disease symptomatology (Han et al 2003;Vicente et al 2012) and even promoters of PWN reproduction and fecundity (Zhao et al 2006).…”
Section: P Pinaster With B Xylophilus Co-cultures Establishmentmentioning
confidence: 99%
“…These results and other findings indicate that bacteria associated with nematodes are essential for disease development (Zhao et al, 2014;Proenc ßa et al, 2017). On the other hand, pine endophytic bacteria were suggested to be part of the plant-nematode interaction by growth promotion or induction of resistance in pine trees (Nascimento et al, 2015). The selected pine endophytic strains 16YSM-E48, 16YSM-P180 and 16YSM-P39 were identified as P. putida, C. pusillum and S. rhizophila, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial species have several roles in disease development, such as their ability to produce phytotoxins that damage plant cells (Han et al ., ). For pine endophytic bacteria, it has been suggested that such bacteria could have a role in induction of plant resistance, possibly by bacterial produced lipases (Nascimento et al ., ; Proença et al ., ). Moreover, analysis of the pine tree microbiome revealed several orthologues for traits related to plant growth promotion and plant defence factors such as chitinases (Alves et al ., ).…”
Section: Introductionmentioning
confidence: 99%